Students Responses Toward the Use of Wordwall Unjumbled Word in Teaching Learning Context - Asri, Ganing Tiyas; Sukmaningrum, Rahmawati; Setiyorini, Laksi (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
English is the most influential language in the world. However, since learning a language is rarely applied in real life, students tend to think that learning this language is unnecessary. In this situation, integrating technology and education education becomes the most crucial part of making the learning process more successful. This article aims to determine the students' responses to using the educational online game Wordwall Unjumbled Word. Qualitative descriptive is used in this research’s design. As the object of the research, the researcher chose 35 students from 11th graders of Social 4 in 10 senior high schools in Semarang. The results of the research are 57,1% agreed that they like the media, 33,6% agreed that the media is enjoyable, 51,4% agreed the media improves their motivation, 57,1% agreed that the media draws their interest, 48,6% agreed that the media made their learning easier, 34,3% stated that the media did not make them stressed, 42,9% agreed that understand the material, 46,7% agreed that the media is easy to be used, 40% agreed that they would use this media in the subsequent learning and 45,7% agreed that the media is appropriate for English learning. The results found in this research should be considered when choosing a suitable media for the English teaching and learning process.